2007
DOI: 10.5565/rev/papers/v83n0.1134
|View full text |Cite
|
Sign up to set email alerts
|

Discursos y estrategias en torno a la conciliación de la vida laboral y familiar en la negociación colectiva

Abstract: ResumenEste artículo tiene como objetivo examinar cinco hipótesis relacionadas con el desarrollo de la Ley de Conciliación de la Vida Laboral y Familiar, su implantación a través de la negociación colectiva y el significado que adopta el concepto de conciliación para los distintos actores sociales. Los resultados de nuestra investigación muestran que, si bien las políticas europeas de empleo han desempeñado un «papel inductor» de dicha temática, ésta ocupa un lugar secundario en la negociación colectiva. A su … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
1
0
3
Order By: Relevance
“…En las Directivas 92/85/CEE de 1992 y la 96/34/CEE de 1996 aparece un intento por reorientar las políticas y relaciones laborales y sociales desde un diálogo social y desde la negociación colectiva, aunque no ocupa un lugar central en la agenda de esta constituyendo temas clásicos como la cuestión salarial, la jornada laboral o la regulación de la inestabilidad laboral. (Carrasquer et al, 2007;Chieregato, 2020).…”
Section: Unión Europeaunclassified
“…En las Directivas 92/85/CEE de 1992 y la 96/34/CEE de 1996 aparece un intento por reorientar las políticas y relaciones laborales y sociales desde un diálogo social y desde la negociación colectiva, aunque no ocupa un lugar central en la agenda de esta constituyendo temas clásicos como la cuestión salarial, la jornada laboral o la regulación de la inestabilidad laboral. (Carrasquer et al, 2007;Chieregato, 2020).…”
Section: Unión Europeaunclassified
“…Past researchers have recognized that WLB initiatives are associated with beneficial results. The benefits which have been associated include reduced absenteeism, improved quality of life, lesser stress, employee job satisfaction and better performance (Scandura and Lankau, 1997;Carrasquer and Martin, 2005). Past research studies have indicated positive consequences of WLB interventions on employee commitment and organizational citizenship behavior (Kopelman et al, 2006).…”
Section: Work-life Balance and Organizational Performancementioning
confidence: 99%
“…However, it should be noted that numerous reports mention the limits of collective bargaining when it comes to promoting the implementation of work-life balance measures in negotiations. Thus, it appears that the low level of representation of women at negotiating tables (as representatives of both trade unions and businesses) and the consideration of work-life balance as a secondary issue compared to other major issues (such as wages or preserving employment levels) means that this is not the most dynamic method of promoting work-life balance (Torres et al, 2008;Carrasquer et al, 2007). In any case, although collective bargaining has shown obvious limitations in this field, the results of our analysis imply that its impact on the implementation of work-life balance measures at businesses may be positive, even if it is only indirectly by improving overall working conditions.…”
Section: Source: Own Workmentioning
confidence: 99%